Side-chain engineering of green color electrochromic polymer materials: toward adaptive camouflage application. Issue 12 (4th March 2016) - Yu, Hongtao; Shao, Shan; Yan, Lijia; Meng, Hong; He, Yaowu; Yao, Chao; Xu, Panpan; Zhang, Xiaotao; Hu, Wenping; Huang, Wei
Abstract : The synthesised electrochromic polymers can exhibit a vegetable-green color at lower applied voltages and a soil-brown color in the oxidized-state, excellent solubility, superhydrophobicity, strong absorption, very fast switching times, and high stability. Abstract : The syntheses of adaptive camouflage devices based on novel side-chain engineered organic electrochromic materials have been demonstrated. Herein we report a molecule engineering approach for the tuning and syntheses of green-brown switchable electrochromic materials and also demonstrate their applications in chameleonic fabric devices. We have also successfully demonstrated the fabrication of chameleonic fabric devices.